Let's Talk About Sex! - Improving sexual health for patients in stroke rehabilitation. Issue 1 (20th November 2015) - Guo, Meiqi; Bosnyak, Stephanie; Bontempo, Tiziana; Enns, Amie; Fourie, Candice; Ismail, Farooq; Lo, Alex
Abstract: Sexual health contributes greatly to quality of life. Research shows that stroke survivors want to learn and talk about sexual health, but are not given information. In keeping with the Canadian Best Practice Recommendations for Stroke Care, this project aimed to provide all stroke rehabilitation inpatients with the opportunity to discuss sexual health concerns with healthcare providers at West Park Healthcare Centre, a rehabilitation and complex continuing care centre in Toronto. Gap analysis conducted via staff member interviews and retrospective chart reviews showed that close to no patients were given the opportunity to discuss sexual health concerns at baseline. Plan-Do-Study-Act (PDSA) methodology was used as the project framework. The changes implemented included a reminder system, standardization of care processes for sexual health, patient-centred time points for the delivery of sexual health discussions, and the development of a sexual health supported conversation tool for patients with aphasia. By the end of the ten month project period and after three PDSA cycles, the percentage of patients provided with the opportunity to discuss sexual health during inpatient rehabilitation increased to 80%. This quality improvement project successfully implemented the Canadian Best Practice Recommendations for Stroke Care with respect to sexual health. Lessons learned included the importance of early baseline data collection and advance planning for tools used in QI projects. Future projects may focus on improving the discussion of sexual health concerns during outpatient stroke rehabilitation.